Remington : the science and practice of pharmacy/ vol II (the practice of pharmachy) - Remington, Joseph P. (Joseph Price), 1847-1918.; Allen, Loyd V., Jr. (London ; Philadelphia : Pharmaceutical Press, 2013)
For more than 100 years, Remington has been the definitive pharmacy reference. It covers the entire scope of pharmacy education from the history of pharmacy and ethics to the particulars of industrial pharmacy and pharmacy practice. This 22nd edition includes 1 year's free individual access to Remington online via MedicinesComplete.
Includes bibliographical references and index.
Keywords: Pharmacy; Drugs -- Handbooks, manuals, etc; Pharmacology -- Handbooks, manuals, etc; Pharmacy -- Practice -- Handbooks, manuals, etc; Drugs; Pharmacology; Pharmacy -- Practice; Handbooks and manuals